Stringent in-silico identification of putative G-protein-coupled receptors (GPCRs) of the entomopathogenic nematode Heterorhabditis bacteriophora - Kundu, Artha (Journal of nematology, 2023)
© 2023 Artha Kundu et al., published by Sciendo.